Remote Sensing of Electric Fields Observed Within Winter Precipitation During the 2020 Investigation of Microphysics and Precipitation for Atlantic Coast‐Threatening Snowstorms (IMPACTS) Field Campaign. Issue 16 (17th August 2021) - Schultz, Christopher J.; Harkema, Sebastian S.; Mach, Douglas M.; Bateman, Monte; Lang, Timothy J.; Heymsfield, Gerald M.; McLinden, Matthew L.; Li, Lihua; Poellot, Michael; Sand, Kendra
Abstract: Aircraft electric fields from NASA's Lightning Instrument Package (LIP) were coupled with other airborne and ground‐based, and in situ measurements to understand electrification in winter clouds that did not produce lightning. The measurements were made during seven research flights by a NASA ER‐2 during the 2020 Investigation of Microphysics and Precipitation for Atlantic Coast‐Threatening Snowstorms (IMPACTS) campaign. Observed total electric field magnitudes were as high as 80 V m −1 and variability in the electric field was observed along the flight path of the ER‐2, indicating horizontal and/or vertical inhomogeneity in the cloud's electrical structure. X‐band airborne radar data indicated 20‐dBZ echo tops above 5 km in regions where electrification exceeded 10 V m −1 . In these regions, 85‐GHz brightness temperatures (TB ) from an airborne radiometer were lower than 265 K, with the lowest TB (∼210 K) associated with ice scattering collocated with the strongest electric fields. In situ microphysical measurements from the NASA P‐3 aircraft on February 7 indicated that regions near strong electric field contained supercooled water, rimed ice hydrometeors, ice water p‐ content as high as 1 g m −3, liquid water content as high as 0.15 g m −3, and supersaturation as high as 3.5%. These observations support the role of mixed phase microphysics in the generation of electric fields in clouds. In three case studies, ground based S‐band polarimetric radar observed depolarization streaks in differential reflectivity near areas where the strongest electrification was observed. This observation reinforces the utility of depolarization streaks to identify areas of electrification prior to lightning occurrence. Plain Language Summary: Electrification of winter clouds is not well characterized unless lightning is observed. The goal of this work is to understand how winter clouds electrify and the microphysical characteristics that support electrification for non‐lightning producing clouds. Using a unique system of aircraft‐based electric field mills, the electric field of winter clouds was measured and compared against radar and in cloud observations of liquid water, ice, temperature, and relative humidity to determine the conditions in which electrification are observed. Results indicate that when ice orientation is observed in radar data, strong electric fields are also within the same volume of the cloud. The impact of this study is that radar data can be used to determine locations where lightning may be possible prior to observed lightning. Key Points: Electrification of winter clouds occurs in the absence of lightning, and mixed phase microphysics is observed near enhanced electric fields Observed electric fields were as high as 80 V m −1 and variability in the electric field was observed along the flight path of the ER‐2 Electrification within winter clouds can be identified using depolarization streaks in differential reflectivity